Lithologic Hydrocarbon Accumulations in the Upper Jurassic Kalazha Formation in the Foreland Slope, the South Marginal Junggar Basin, Northwest China - Liu, Gang; Qi, Xue-Feng; Li, Jian-Zhong; Zhu, Ming; Yuan, Bo; Pang, Zhi-Chao (Frontiers in Earth Science, 2022)
The foreland slope in the south marginal Junggar Basin (SMJB) is geologically favorable for mass lithologic oil and gas reservoir accumulation. Based on outcrops, thin sections, individual-well facies, and cross-well stratigraphic correlation, the stratigraphic distribution and features of the Upper Jurassic Kalazha Formation were investigated in the SMJB. There are two sedimentary sources in the southwest and southeast Kalazha Formation, which thin out from south to north and vanish in the northern slope. Fan deltas occur in the southwest, and braided river deltas occur in the southeast. Kalazha reservoir rocks and sedimentary facies were predicted using joint 2D and 3D seismic impedance inversion. According to the overall analysis, the Kalazha Formation in the foreland slope is favorable for hydrocarbon accumulation, considering structural highs as the destination of long-term hydrocarbon migration and the updip wedge-out zone in the north with potential lithologic traps. The accumulation model was established with source rocks, reservoir rocks, caprocks, and migration systems for the lithologic hydrocarbon reservoirs in the Kalazha Formation in the SMJB. As per the model and regional stratigraphic and structural features, Kalazha lithologic hydrocarbon reservoirs mainly formed in the annular updip wedge-out zone in the foreland slope. Our deliverables may provide useful information for mass lithologic hydrocarbon accumulation in the foreland slope and deep to ultra-deep hydrocarbon exploration in the SMJB.